RESEARCH ANO TECHNOLOGY BUSINESS INCUBATORS IN THE UNIVERSITY - Arroyo, J. (2010)
Due lo the importance of conveying the results of university research lo the community, the Vice Rector of Research of San Marcos University is considering taking advantage of such research through the implementation of productive enterprises. To this end we present a business model for technology-based incubators.